Characterization and modeling of additively manufactured Ti-6Al-4V alloy with modified surfaces for medical applications - Kök, Hüray Ilayda; Andreeva, Tonya; Stammkötter, Sebastian; Reinholdt, Cindy; Akbas, Osman; Jahn, Anne; Gamon, Florian; Fuest, Sandra; Teschke, Mirko; Schäfer, Miriam; Müller, Michael; Koch, Alexander; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
In the field of biomedical implants, additively manufactured titanium alloys, particularly Ti-6Al-4V, hold significant potential due to their biocompatibility and mechanical properties. This study focuses on the characterization and modeling of additively manufactured Ti-6Al-4V alloy for dental and maxillofacial implants, emphasizing fatigue behavior, surface modification, and their combined effects on cyto- and osseocompatibility. Experimental methods, including tensile, compression, and fatigue testing, were applied alongside in silico simulations to assess the long-term mechanical performance of the material. Surface properties were further modified through sandblasting and coating techniques to enhance cell adhesion and proliferation. By using in-vitro methods, the cytocompatibility of the coatings and materials was examined followed by in-vivo tests to determine osseocompatibility. Results demonstrated that appropriate surface roughness and modifications are essential in optimizing osseointegration, while the layer-by-layer additive manufacturing process influenced the fatigue life and stability. These findings contribute to the development of patient-specific implants, optimizing both mechanical integrity and biological integration for enhanced clinical outcomes. This work summarizes the investigations on additively manufactured Ti-6Al-4V alloy of the research unit 5250 “Mechanism-based characterization and modeling of permanent and bioresorbable implants with tailored functionality based on innovative in vivo, in vitro and in silico methods” funded by the Germany Research Foundation (DFG).